Pengaruh Variasi Jarak Alur Setengah Lingkaran Terhadap Penguatan Vorteng dan Penurunan Tekanan Pada Saluran Berpenampang Segi Empat - Purnami, Purnami (Rekayasa Mesin, 2010)
This research was done by implementing a closed square cross section channel, where the bottom surface of the channel was semicircle transverse grooved. The frequency of flow oscillation measurement was done by setting up a resistance sensor that is Wheatstone bridge. A resistor of the Wheatstone bridge is place in to a manometer which was filled by water. The manometer is connected to the channel while the sensor is connected to ADC. A U manometer was used to measure the static pressure. Both measurements were done together at severals Reynold number. Based on the result it is seen that the maximum Strouhal number at Reynold number of 950. Vortex strength increases when Strouhal number increase where the largest vortex strength occurs at the smallest grooved distance with the increase of pressure drop. Oscillating shear stress increase with the increase of Reynold number. This phenomena indicated that highly transport momentum occurs as the Reynold number increase which it is contributed to the vortex strength and fluid exchange. Keywords : vortex, Reynold